Literature Review: Analysis of Ki Hajar Dewantara's Concept of Education - Lika Widiawati; Herman Nirwana; Dina Sukma (Manajia: Journal of Education and Management, 2024)
This study examines the educational concepts of Ki Hajar Dewantara through a literature review. Ki Hajar Dewantara is an Indonesian educational figure known for his deep views on emancipatory education and the education of the nation's children. This study analyzes various literature discussing the ideas, philosophy, and implementation of Ki Hajar Dewantara's educational concepts. The literature review findings indicate that Ki Hajar Dewantara's educational concepts emphasize character formation, independence, and a balance between intellectual and moral development. The conclusion of this study highlights the relevance and importance of Ki Hajar Dewantara's educational concepts in the context of modern education in Indonesia.